Značaj obnove bosanskohercegovačke državnosti na prvom zasjedanju ZAVNOBiH-a / Importance of Renewal of BIH Statehood at the First Session of ZAVNOBiH (National Anti-Fascist Council of the People's Liberation of Bosnia and Herzegovina) - Kurtćehajić, Suad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
The first Session of ZAVNOBiH in Mrkonjić Grad, held on 25 and 26 November 1943, was historical event for Bosnia and Herzegovina. For the first time after 480 years since Bosnia had lost its statehood by the Ottoman Empire in 1463, representatives of all nations in Bosnia and Herzegovina met to freely and willfully decide on its destiny. In this regard, 173 councilors, elected out of 247 ZAVNOBiH delegates postured on Bosnia and Herzegovina by formulation included in ZAVNOBiH Resolution under the item 5 where the will of the people of Bosnia and Herzegovina was expressed. Their country, that is not neither Serbian or Croatian or Muslim, but Serbian, Croatian and Muslim should be free and united Bosnia and Herzegovina where full equality and parity of Serbs, Muslims and Croats will be ensured. In this way the principle of ideal co-ownership on the territory of Bosnia and Herzegovina was proclaimed. On the other hand, this means that there are no people that live in Bosnia and Herzegovina that have exclusivity on any inch of it. In this way the foundations of the new Statehood of Bosnia and Herzegovina were laid. This Statehood was achieved in the Yugoslav federation but in the situation of Yugoslav crisis that ended with the dissolution, proved to be the most important fact for Bosnia and Herzegovina's independence, what happened at the beginning of 1992.